Expression of anti-chikungunya single-domain antibodies in transgenic Aedes aegypti reduces vector competence for chikungunya virus and Mayaro virus - Webb, Emily M.; Compton, Austin; Rai, Pallavi; Chuong, Christina; Paulson, Sally L.; Tu, Zhijian; Weger-Lucarelli, James (Frontiers in Microbiology, 2023)
Chikungunya virus (CHIKV) and Mayaro virus (MAYV) are closely related alphaviruses that cause acute febrile illness accompanied by an incapacitating polyarthralgia that can persist for years following initial infection. In conjunction with sporadic outbreaks throughout the sub-tropical regions of the Americas, increased global travel to CHIKV- and MAYV-endemic areas has resulted in imported cases of MAYV, as well as imported cases and autochthonous transmission of CHIKV, within the United States and Europe. With increasing prevalence of CHIKV worldwide and MAYV throughout the Americas within the last decade, a heavy focus has been placed on control and prevention programs. To date, the most effective means of controlling the spread of these viruses is through mosquito control programs. However, current programs have limitations in their effectiveness; therefore, novel approaches are necessary to control the spread of these crippling pathogens and lessen their disease burden. We have previously identified and characterized an anti-CHIKV single-domain antibody (sdAb) that potently neutralizes several alphaviruses including Ross River virus and Mayaro virus. Given the close antigenic relationship between MAYV and CHIKV, we formulated a single defense strategy to combat both emerging arboviruses: we generated transgenic Aedes aegypti mosquitoes that express two camelid-derived anti-CHIKV sdAbs. Following an infectious bloodmeal, we observed significant reduction in CHIKV and MAYV replication and transmission potential in sdAb-expressing transgenic compared to wild-type mosquitoes; thus, this strategy provides a novel approach to controlling and preventing outbreaks of these pathogens that reduce quality of life throughout the tropical regions of the world.